Major Histocompatibility Complex I and II Expression and Lymphocytic Subtypes in Muscle of Horses with Immune‐Mediated Myositis. (28th June 2016) - Durward‐Akhurst, S.A.; Finno, C.J.; Barnes, N.; Shivers, J.; Guo, L.T.; Shelton, G.D.; Valberg, S.J.
Abstract : Background: Major histocompatibility complex (MHC) I and II expression is not normally detected on sarcolemma, but is detected with lymphocytic infiltrates in immune‐mediated myositis (IMM) of humans and dogs and in dysferlin‐deficient muscular dystrophy. Hypothesis/Objectives: To determine if sarcolemmal MHC is expressed in active IMM in horses, if MHC expression is associated with lymphocytic subtype, and if dysferlin is expressed in IMM. Animals: Twenty‐one IMM horses of Quarter Horse‐related breeds, 3 healthy and 6 disease controls (3 pasture myopathy, 3 amylase‐resistant polysaccharide storage myopathy [PSSM]). Methods: Immunohistochemical staining for MHC I, II, and CD4+, CD8+, CD20+ lymphocytes was performed on archived muscle of IMM and control horses. Scores were given for MHC I, II, and lymphocytic subtypes. Immunofluorescent staining for dysferlin, dystrophin, and a‐sarcoglycan was performed. Results: Sarcolemmal MHC I and II expression was detected in 17/21 and 15/21 of IMM horses, respectively, and in specific fibers of PSSM horses, but not healthy or pasture myopathy controls. The CD4+, CD8+, and CD20+ cells were present in 20/21 IMM muscles with CD4+ predominance in 10/21 and CD8+ predominance in 6/21 of IMM horses. Dysferlin, dystrophin, and a‐sarcoglycan staining were similar in IMM and control muscles. Conclusions and clinical importance: Deficiencies of dysferlin, dystrophin, and a‐sarcoglycan are not associated with IMM. Sarcolemmal MHC I and II expression in a proportion of myofibers of IMM horses in conjunction with lymphocytic infiltration supports an immune‐mediated etiology for IMM. The MHC expression also occured in specific myofibers in PSSM horses in the absence of lymphocytic infiltrates.